Urban design parameters for heat mitigation in tropics. (December 2020) - Jamei, E.; Ossen, D.R.; Seyedmahmoudian, M.; Sandanayake, M.; Stojcevski, A.; Horan, B.
Abstract: According to United Nations, cities situated in the tropical belt occupy only 36% of the Earth's surface yet account for 1/3 of the entire global population. The increasing number of compact dense cities and the rapid population growth in the tropics have also been accompanied by increased urban air temperature. Increased air temperature is often associated with heat waves, and increased energy consumption. Therefore, the urban heat island (UHI) phenomenon and thermal stress have received much research attention and, as a result, the establishment of heat mitigation technologies has become critical. Although studies on urban climate in the tropics have shown progress, the situation in these areas remains complex and warrants further investigation. Accordingly, this paper examines the available heat mitigation techniques and their effectiveness in tropical areas from five perspectives, namely, shading (modifications in urban geometry), urban ventilation (street orientation, sun, and wind), urban greening (green roofs, trees, parks, and walls), albedo, and water bodies. This review paper showed that adopting a combination of mitigation approaches is the most effective method in reducing temperature in tropical cities. The use of shading and/or urban ventilation has also been proven to be more promising than the extensive use of vegetation, water bodies, or albedo modifications in reducing air temperature in tropical cities, where there is already a high level of humidity exists. Some key planning actions to combat UHI and thermal discomfort in tropical areas are eventually provided that can help urban planners integrate urban climatic knowledge into their practices. Highlights: The rapid urbanization in tropics has caused a significant level of urban warming. Despite the progress in tropical urban climate research, the situation in these regions remains complex and warrants further investigation. Different heat mitigation methods including shading, urban ventilation, city greening, albedo, and use of water bodies were explored. The most effective approach for reducing the heat in tropics is the combined approach, and shading and/or urban ventilation is more promising than extensive urban greening, use of water bodies, or albedo alteration in reducing air temperature in tropics where there is already a high level of humidity exists.